Internal Stigma of an HIV-Infected Housewife: a Phenomenological Study - Wisotowardono, Ossie Sosodoro; Ahmad, Riris Andono; Prabandari, Yayi Suryo; Hakimi, Mohammad (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2017)
In connection with the transmission of the HIV virus, housewives may have experienced internal stigma, which can have an effect on HIV prevention and the treatment of AIDS. Twenty-three HIV-infected housewives were interviewed in a qualitative study conducted in North Jakarta. The data were analyzed using a phenomenological approach. Seven themes emerged to explore internal stigma housewives and to compose the essence of the internal stigma. The essence of an HIV-infected housewife who has internalized the stigma can be illustrated as an Indonesian proverb which is â€œHidup Segan Mati Tak Mauâ€ or in English can be interpreted as â€˜having lost the will to live, but not wanting to dieâ€™. This could explain that AIDS forces them to live in anxiety in all aspects of life but as housewives, they must keep thinking about continuing life especially with regard to the future of their beloved children.